At finde vej ud af verden: Død, sprog og poststrukturalisme i Karl Ove Knausgårds Min kamp - Elholm Andersen, Claus (Tidskrift för litteraturvetenskap, 2014)
A Way Out of the World. Death, Language, and Post-structuralism in Karl Ove Knausgård’s My Struggle In this article, I present a close reading of Karl Ove Knausgård’s My Struggle. My point of departure is Knausgård’s reflections upon death presented in the very first pages of the first of this six-volume novel. I read these reflections as thoughts regarding the issue of form and content, and as an introduction to one of the main themes in the novel. Thus, I argue that, throughout this novel, Knausgård tries to unite form and content, and that this is the central struggle referred to in the work’s title.